Long-Term Mortality Analysis in Parkinson's Disease Treated with Deep Brain Stimulation. (3rd March 2014) - Rocha, Sofia; Monteiro, Ana; Linhares, Paulo; Chamadoira, Clara; Basto, Margarida Ayres; Reis, Carina; Sousa, Cláudia; Lima, Joana; Rosas, Maria José; Massano, João; Vaz, Rui
Abstract : Background. Few data have been published regarding long-term mortality in patients with Parkinson's disease treated with DBS. Methods. This study analyzed long-term mortality rates, causes, and correlates in PD patients treated with DBS. Results. 184 consecutive patients were included; mean follow-up was 50 months. Fifteen deaths occurred (total 8.15%, annual mortality rate 1.94%). Mean age at disease onset and at surgery was48 ± 2.4 and63 ± 1 . 6 years, respectively. Mean disease duration until death was21 ± 7.8 years. Most deaths related to stroke, myocardial infarction, other vascular/heart disorders, or severe infection; one suicide was recorded. Deceased PD patients were mostly male and had lower motor benefit after DBS, but univariate analysis failed to show significant differences regarding gender and motor benefit. Survival was 99% and 94% at 3 and 5 years. Conclusions. Long-term survival is to be expected in PD patients treated with DBS, possibly higher than previously expected. Death usually supervenes due to vascular events or infection.